The Bacchae and other plays - Euripides (Penguin Books, 1961)
Ion.–The women of Troy.–Helen.–The Bacchae
Die Vorlage enth. insgesamt 4 Werke
Keywords: Euripides; Ion; Hecuba; Helen; Pentheus; Dionysus; Bacchantes